Tanggung Jawab Hukum Pemerintah Daerah dalam Implementasi Peraturan Daerah Nomor 3 Tahun 2016 tentang Kesesuaian Penggunaan Lahan di Kabupaten Labuhanbatu - Farhan Syani Natama Hrp; Elvira Dewi Ginting (Jurnal Hukum Lex Generalis, 2025)
This study analyzes the implementation of Regional Regulation (Perda) No. 3 of 2016 on the Spatial Planning (RTRW) of Labuhanbatu Regency in regulating land-use conformity. The main problems identified include the operation of factories outside designated industrial zones and the existence of electricity towers without permits in accordance with the regulation. The aim of this research is to examine the implementation of Perda No. 3 of 2016 and to analyze the mechanisms of legal responsibility as well as the role of the government in addressing spatial planning violations. The study employs a normative juridical method with statutory and conceptual approaches. Data were collected through library research and analyzed descriptively and qualitatively, using primary legal materials in the form of legislation and secondary legal materials such as legal journals and books. The findings reveal that the implementation of Perda No. 3 of 2016 has not been optimal. Systemic violations were discovered, including the operation of a palm oil factory in Rantau Utara District, which should have been located in the designated industrial area of Rantau Selatan District, as well as the construction of electricity towers without permits. Regarding legal responsibility, the study found inconsistencies in law enforcement, where the local government showed strict responses to violations concerning electricity towers but remained passive in addressing violations by the palm oil factory. The study concludes that the success of RTRW implementation requires strong political will, consistent law enforcement, and the commitment of all stakeholders to realize sustainable and equitable spatial planning in Labuhanbatu Regency.